DOI: 10.31274/etd-180810-4342
|View full text |Cite
|
Sign up to set email alerts
|

Climate-smart agriculture in Midwest cropping systems: evaluating the benefits and tradeoffs of cover crops

Abstract: This work is dedicated to the future generations of the great state of Iowa, where I have been happy to call home. In particular, I look to the 7 th graders at Brody Middle School in Des Moines who I helped teach from 2014-2015, that they may be the future leaders that have the courage, wisdom and foresight to protect the state's rich resources and create a better world for all. iii

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 140 publications
1
6
0
Order By: Relevance
“…Yield predictions resulted in non-significant differences for both maize (p=0.92) and soybean (p=0.94) between the cover crop and no cover treatments over the simulation period (2015 to 2060). Over the period of model calibration (2003-2008) and validation (2009-2014), there were also not any years at the research site where there were statistically different crop yields between the cover and no cover crop treatment (Kaspar et al, 2007;Kaspar et al, 2012;Basche, 2015). This level of agreement with the field data gives us confidence in our predictions for yield differences between the two treatments.…”
Section: Cover Crop Impacts On Maize and Soybean Yieldssupporting
confidence: 62%
See 2 more Smart Citations
“…Yield predictions resulted in non-significant differences for both maize (p=0.92) and soybean (p=0.94) between the cover crop and no cover treatments over the simulation period (2015 to 2060). Over the period of model calibration (2003-2008) and validation (2009-2014), there were also not any years at the research site where there were statistically different crop yields between the cover and no cover crop treatment (Kaspar et al, 2007;Kaspar et al, 2012;Basche, 2015). This level of agreement with the field data gives us confidence in our predictions for yield differences between the two treatments.…”
Section: Cover Crop Impacts On Maize and Soybean Yieldssupporting
confidence: 62%
“…Although there was a non-significant maize yield reduction in the cover crop treatment, our analysis of the soil water record indicated higher moisture levels at 5-cm, 15-cm and 30-cm depths during the grain fill period for maize (Basche, 2015). Even with the competition for soil water predicted by APSIM in the very dry seasons, yield reductions predicted in the cover crop treatment are relatively small in these years.…”
Section: Wet and Dry Year Analysismentioning
confidence: 53%
See 1 more Smart Citation
“…The late cover crop termination in system (B) prevented an early soybean sowing date, which is needed for achieving high yields in no-tillage herbicide-free systems. Previous research suggested strategies to allow an earlier planting date, i.e., using earlier-flowering rye cultivars [17,28], planting rye earlier [10,26,[29][30][31], planting soybean at the boot stage of rye cultivars with low regrowth potential [32,33], and planting soybean into standing rye prior to termination.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Flower et al [10] indicated that late killing of the cover crop reduces soil water storage. While cover crops are known to improve water retention (especially during winter), they are not able to offset crop yield declines that may occur because of temperature and water stress [19,30].…”
Section: Soybean Productivitymentioning
confidence: 99%